CT-Guided Percutaneous Core Needle Biopsy of Small Pulmonary Nodules (< 2 cm): How Efficient is it as a Diagnostic Tool in Ruling Out Metastatic Disease? - Lingegowda, Dayananda; Agrawal, Manisha; Chatterjee, Argha; Ghosh, Priya; Khoda, Jeevitesh; Gehani, Anisha; Sen, Saugata; Mukhopadhyay, Sumit; Chandra, Aditi; Patra, Anurima (Indian Journal of Radiology and Imaging, 2025)
Incidentally detected small pulmonary nodules in patients with an underlying malignancy most often warrant sampling. Biopsy from such small pulmonary nodules (< 2 cm) is challenging. In this study, we aim to evaluate the accuracy of computed tomography (CT)-guided percutaneous core needle biopsy (CNB) of small pulmonary nodules.A total of 169 patients who had CT-guided percutaneous CNB for small pulmonary nodules (less than 2 cm) between January 2015 and December 2018 were the subjects of this retrospective, single-center investigation. We determined the success rate of CNB and the rate of a diagnostic biopsy. Calculations were made for a multivariate study of the risk variables for complications, such as pneumothorax and pulmonary hemorrhage.The success rate of lung biopsy, defined by obtaining a sample of pathologically reportable quality, was 92.9% (157/169). A malignancy was diagnosed in 60.4% of cases (102/169). Pneumothorax developed in 21.9% cases (37/169), with only 5.3% (9/169) patients requiring treatment (8 needle aspirations and 1 pigtail catheter drainage). Use of a thicker (18G) biopsy needle was the only statistically significant predictor of pneumothorax (odds ratio 2.61, 95% confidence interval 1.24–5.51, p = 0.01). Perifocal hemorrhage was common (72.2%, 122/169) but clinically significant pulmonary lobar hemorrhage was seen only in 6.5% of the cases (11/169). One patient required intensive care unit admission due to desaturation from aspiration of blood.CT-guided biopsy of small pulmonary nodules is safe and feasible with a good success rate.
Keywords: CT-guided biopsy; lung metastasis; small pulmonary nodules